Age features of myocardial remodeling in men with ischemic chronic heart failure and renal dysfunction - D. A. Lashkul (Zaporozhye State Medical University, 2014)
In recent years, medicine has faced the problem of "dual epidemic" of heart and kidney failure. Regardless of the degree of heart failure, chronic kidney disease increases the risk of death and cardiac decompensation. Left ventricular hypertrophy (LVH) is a well known option of cardiac remodeling and it has higher prevalence among people with impaired renal function. Types of myocardial remodeling identify mortality risk of patients with cardiovascular complications. We know that gender and age are important risk factors for cardiovascular disease. However, in most studies structural remodeling of the myocardium was analyzed without sex and age characteristics. The aim of research is to study the age features of the formation of different types of myocardial remodeling in men with ischemic chronic heart failure and renal dysfunction. Materials and methods. To investigate the age characteristics of cardiac remodeling in men with ischemic chronic heart failure and renal dysfunction structural and functional remodeling of left ventricular myocardium was studied in 277 men (mean age 58,1±9,3 years) using Doppler echocardiography. Depending on the glomerular filtration rate, patients were divided into 3 groups: 58 with normal GFR (>90 ml/min/1.73m2), 182 with a slight decrease in GFR (60-90 ml/min/1.73m2) and 37 with moderately reduced GFR (<60 ml/min/1.73m2). Echocardiography was performed using the General Electric VIVID 3 system (General Electric Healthcare, USA) with the 2.5-3.5 MHz transducer and Doppler technique. Descriptive statistics are presented as mean±standard deviation for continuous variables and as percentages for categorical variables. Depending on the distribution of the analyzed parameters unpaired Student's t-test or U-Mann-Whitney test were used. Comparisons among all groups for baseline clinical variables were performed with the Pearson χ2 or Fisher exact test for categorical variables. Differences were considered reliable for values of p<0,05. Results. Based on the results of our study in 58 (20.9%) men renal dysfunction was not found, in 182 (65.8%) slight decrease and in 37 (13.3%) moderate reduction of renal function were found. To determine the effect of age on remodeling, we divided all the patients into two age groups: 60 years (middle age) - 166 (59.9%) and men older than 60 years (old age) - 111 (40.1%) people. When comparing the groups of middle-aged and elderly it was found that normal renal function was in 45 (27.1%) and 13 (11.7%) persons, respectively (χ2=11,2; p=0.0008), light kidney dysfunction was in 108 (65.1%) and 74 (66.7%) persons, respectively (χ2=0,8; p=0.78), moderate dysfunction was in 13 (7.8%) and 24 (21.6%) people, respectively (χ2=10,9; p=0.0009). In analyzing the types of LV remodeling in patients with heart failure and mild decrease in GFR normal geometry (9.3% vs. 2,7%; χ2=3,07; p=0.08), concentric remodeling (2.8% vs. 5,4%; χ2=0,82; p=0.37), concentric hypertrophy (44.4% vs. 40,5%; χ2=0,27; p=0.6), eccentric hypertrophy (43.5% vs. 51,4%; χ2=10,8; p=0.29) were revealed. However, at lower eGFR less than 60ml/min/1,73m2 in single patients normal geometry and concentric remodeling were revealed, concentric hypertrophy (23.1% vs. 50%; χ2=2,54; p=0.11), eccentric hypertrophy (76.9% vs. 50%; χ2=2,54; p=0.11). Thus, their data are consistent with the other studies, where the change in LV geometry in patients with chronic heart failure with progressive decline in renal function was revealed in favor of decrease of patients with the normal type of geometry, concentric remodeling and increase of patients with eccentric as one of the most unfavorable type of remodeling. Conclusion. In men with ischemic chronic heart failure in middle age in 7.8% and in old age in 21.6% of cases a moderate decrease in renal function is found. In men with ischemic chronic heart failure, regardless of age eccentric and concentric remodeling of the left ventricle occur equally often, in moderate decrease in renal function in middle age category concentric LV hypertrophy dominates and in elderly men eccentric and concentric hypertrophy are found equally common. Perspective is considered to take into account gender-age features of myocardial remodeling with a view to the appointment of a differentiated approach in the treatment of patients with ischemic chronic heart failure and renal dysfunction.